Quality green energy supply chain management practices in Malaysian / Argustina Zainuddin...[et al.] - Zainuddin, Argustina; Kuzaiman, Nur Asiah; Mohd Salleh, Noor Azlina; Kasolang, Salmiah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This study proposed the integrated framework consisted of the supply chain management system of Total Quality Management System(TQM), Lean Manufacturing(LM) and Green Management System (EMS) with the Energy Management System(EnMS) policy. The objective of the system is to provide the organization a way to improve their environmental, energy and economic performance, which also would impact on their operational performance. A survey questionnaire was developed and distributed to 30 highly active and recommended automotive vendors in Malaysia by Malaysian Automotive Institute (MAI) and the data was analyzed by using Statistical Package for the Social Sciences (SPSS) v.19. From the survey, it was found that most vendors have been practicing TQM, LM and EMS due to customer requirement, however, there only a few vendors that are aware of Energy Management System (EnMS). This study focuses only on highly active companies that involved in MAJAICO program and the Proton Vendor Development Program. The objective of this research is to study on the status of integrated management system in the automotive companies. The proposed framework practice includes green purchasing, green manufacturing, materials management, green distribution/marketing and reverse logistics). This is the preliminary study of integrating Energy Management System in managing and design a new framework toward a sustainable environment. Besides, to promote less consumption of energy in order to preserve a better future for the next generation. The future studies can be steered to access the status of supply chain management practices in other companies and industries.